ENHANCING THE LOCAL SUSTAINABILITY THROUGH CREATING SHARED VALUE (LOCUS OF RESEARCH ON GARUT LEATHER HANDCRAFT) - Dharmawan, Steven Emmanuel; Setiawan, Temy; Luckianto, Marvin (Jurnal Akuntansi Bisnis, 2025)
Background: Business actors in the leather crafting MSME sector in Garut have yet to optimize performance, despite increasing awareness of social and environmental business values.Objective: The objectiveof this research is to examine whether Creating Shared Value (CSV) moderates the relationship between Entrepreneurial Orientation and both financial and non-financial performance among Micro, Small, and Medium-Sized Enterprises (MSMEs) in the leather crafting sector in Garut.Research Methods: The research method used a quantitative approach using a survey conducted on MSMEs in the leather crafting sector in Garut that have been operating for more than six months. Data were collected from a selected sample and analyzed to examine the relationships between Entrepreneurial Orientation, Creating Shared Value, and both financial and non-financial performance.Research Results: The research found that entrepreneurial orientation has no significant impact on the financial performance of MSMEs. However, it significantly enhances non-financial performance, such as social and environmental outcomes. Additionally, creating shared value does not moderate the relationship between entrepreneurial orientation and MSME performance.Originality/Novelty of Research: To the best of the researcher's knowledge, no previous research has specifically explored the relationship of entrepreneurial orientation to financial and non-financial performance, especially in terms of the environment related to sustainability and MSMEs leather craftsmen in Garut.